Optimizing Melon Seed Decortication: A Taguchi-Based Approach for Single and Multi-Objective Performance - Tsapi Kevin; Magnou Ekokem (Indonesian Journal Publisher, 2026)
This study was conducted to optimise the parameter sets for a melon seed shelling machine. The parameter sets are motor speed and moisture content with different levels were experimented and analysed to build mathematic models. The objective was to describe the relationship between the inputs parameter values and the outputs (shelling efficiency, breakage percentage and machine capacity). Single-objective and multi-objective models were constructed and studied to identify the optimal set, optimal trade-off set of parameters. Minitab software aid for analysis and decision-making. The optimisation revealed a significant trade-off between single objectives) (optimal settings for maximising shelling efficiency (96.7%), minimising seed breakage (1.41%), and maximising capacity (53.98 kg h-1) were mutually exclusive. Multi-objective analysis identified moisture content as the statistically dominant factor (p < 0.05), with motor speed being insignificant. The validated optimal parameter combination for balanced performance was moisture content of 26% and a motor speed of 2100 rpm, which simultaneously improved all three key performance metrics. The proposed solutions for handling single- and multi-objective optimisation through the framework are practical and can be extended to other post-harvest processing equipment.